2014
DOI: 10.1074/jbc.m114.571703
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity and Evolution of (+)-3-Carene Synthase and (−)-Sabinene Synthase Functions of a Sitka Spruce Monoterpene Synthase Gene Family Associated with Weevil Resistance

Abstract: Background: (ϩ)-3-Carene/(Ϫ)-sabinene synthases are associated with insect resistance in Sitka spruce. Results: Amino acid position 596 is critical for the monoterpene synthase product profile. Conclusion: This work revealed mechanistic underpinnings for patterns of functional evolution of this monoterpene synthase family. Significance: Catalytic plasticity of conifer monoterpene synthases is a major factor in the diversification of the TPS-d family and evolution of insect resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 30 publications
0
61
1
Order By: Relevance
“…Of terpene‐related genes, the monoterpene synthases TPS‐Car and TPS‐Lim were significantly up‐regulated in MeJA‐treated trees as compared with control, but not in fungus‐inoculated trees (Figure b). Surprisingly, there was no correspondence between up‐regulation of these two specific monoterpene synthases in MeJA‐treated trees and levels of their metabolic products (considered to be 3‐carene and terpinolene for TPS‐Car, Roach, Hall, Zerbe, & Bohlmann, , and (−)‐limonene for TPS‐Lim, Martin, Fäldt, & Bohlmann, ). As shown in Figure , none of the major products of these monoterpene synthases increased significantly in MeJA‐treated trees relative to the control, neither at 14 nor 35 days after treatment.…”
Section: Resultsmentioning
confidence: 97%
“…Of terpene‐related genes, the monoterpene synthases TPS‐Car and TPS‐Lim were significantly up‐regulated in MeJA‐treated trees as compared with control, but not in fungus‐inoculated trees (Figure b). Surprisingly, there was no correspondence between up‐regulation of these two specific monoterpene synthases in MeJA‐treated trees and levels of their metabolic products (considered to be 3‐carene and terpinolene for TPS‐Car, Roach, Hall, Zerbe, & Bohlmann, , and (−)‐limonene for TPS‐Lim, Martin, Fäldt, & Bohlmann, ). As shown in Figure , none of the major products of these monoterpene synthases increased significantly in MeJA‐treated trees relative to the control, neither at 14 nor 35 days after treatment.…”
Section: Resultsmentioning
confidence: 97%
“…Resistance of lodgepole pine against the mountain pine beetle involves quantitative multigenic control (Yanchuk et al ., 2008), and may be based on a suite of chemical and physical defences (Franceschi et al ., 2005; Bohlmann, 2012). In Sitka spruce, resistance to the white pine weevil has been associated with variations of stone cells and resin ducts (King et al ., 2011) and constitutive and induced terpenoid levels and their underlying terpenoid synthases (Hall et al ., 2011; Roach et al ., 2014). The present study showed that levels of both Pgβglu-1 transcripts and acetophenone aglycons active against the SBW are elevated in early summer when the most destructive SBW larval stages are active (Miller, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…coli strain BL21DE3-C43 for heterologous protein expression, as previously described [29]. Recombinant protein was purified using the GE healthcare His SpinTrap kit (www.gelifesciences.com) according to manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%